Snakes and ladders: differential patterns of post-reform social mobility in Siping, north-east China. Issue 3 (2nd September 2018) - Liu, Dong; Hamnett, Chris
ABSTRACT: This analysis of the relative winners and losers from economic and social change in post-reform China focuses on the small, fourth-tier city of Siping, north-east China. Following Louis Chauvel's work in France, the impact of economic transformation on different age cohorts is examined, and a 'lucky generation' is identified, made up notably of those born between the mid-1960s and the mid-1980s, who were educated and whose working lives coincided with the expansion of economic and social opportunities in the reform era. Its fortunes are contrasted with other age cohorts and with the groups formerly employed in north-eastern rust-belt states and collectively owned enterprises, rural dwellers and rural–urban migrants.